AZ IDEGENSÉGTAPASZTALAT A PALATICS-KÓDEX NÉHÁNY ÉNEKÉBEN: A KÓDEX MADZSARI TÜRKI: A NEM BÁNTOM ÉN TE KEGYELMED... KEZDETŰ MAKARONIKUMÁNAK ÉS A HIRVAT TÜRKISZI CÍMŰ ÉNEKÉNEK ÖSSZEVETŐ ÉRTELMEZÉSE. - UTASI, Csilla (ANAFORA, 2026)
The unknown compiler of the Palatics Codex, which dates from the last quarter of the sixteenth century from the territory of the Ottoman rule, recorded German-Hungarian-Croatian and Latin texts in Arabic characters. The Hungarian poem Maĝari türki and the Croatian poem Chirwat turkisi stand out from other German and Hungarian songs in the codex in that they are composed in Turkish verse. There is an almost unanimous agreement among critics that the two poems were written by poets who had converted to Islam and composed in their mother tongue. This paper proposes a new interpretation. Accordingly, the Maĝari türki and the Chirwat türkisi poems should be regarded as stylistic imitations which—together with the Turkish-Hungarian macaroni poem attached to them—represent and resolve the cultural shock of Ottoman rule at the level of erotic relationships.